Accelerating market diffusion of battery electric vehicles through alternative mobility concepts. (1st January 2014) - Fojcik, Thomas M.; Proff, Heike
To analyse how consumer acceptance and willingness to pay and thus how the market diffusion of battery electric vehicles could be accelerated, we introduce different mobility concepts in conjunction with single battery electric vehicle offers and test possible effects on consumer acceptance and willingness to pay. Our exploratory analysis of 2, 623 private consumers in Germany reveals that battery electric vehicles already find acceptance. More than half of the respondents are positive about battery electric vehicles. The other half is either undecided or critical. The willingness to pay for battery electric vehicles is around 5, 000 and up to 10, 000 EUR below current market prices in Germany. However, our results also indicate that consumer acceptance and willingness to pay for battery electric vehicles can be stimulated by a link with some, but not all mobility concepts. Thus, the market diffusion of battery electric vehicles could be accelerated by linking battery electric vehicles with different mobility concepts in the future.